2017
DOI: 10.1186/s12957-017-1119-2
|View full text |Cite
|
Sign up to set email alerts
|

Are there intra-operative hemodynamic differences between the Coliseum and closed HIPEC techniques in the treatment of peritoneal metastasis? A retrospective cohort study

Abstract: BackgroundAlthough two main methods of intraoperative hyperthermic intraperitoneal chemotherapy (HIPEC) are currently accepted, the superiority of one over the other has not yet been demonstrated. The purpose of this study was to determine whether there are hemodynamic and temperature differences between patients who received HIPEC in two different techniques, open versus closed abdomen.MethodsThis retrospective study was conducted in our center between 2011–2015 in 30 patients who underwent surgery for perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
0
16
0
3
Order By: Relevance
“…Nine studies were identified that evaluated HIPEC related morbidity, mortality, drug penetration, and distribution [46, 51, 52, 55, 59, 60, 62, 67, 68]. Two main HIPEC techniques are employed: the open abdomen (Coliseum) technique and the closed abdomen technique.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were identified that evaluated HIPEC related morbidity, mortality, drug penetration, and distribution [46, 51, 52, 55, 59, 60, 62, 67, 68]. Two main HIPEC techniques are employed: the open abdomen (Coliseum) technique and the closed abdomen technique.…”
Section: Resultsmentioning
confidence: 99%
“…Another argument for open HIPEC is the ability for better temperature homogeneity[ 7 ]. On the other hand, a downside of open HIPEC is achieving and maintaining hyperthermic temperatures given the dissipation of heat from the open abdomen[ 10 ]. Our study would suggest that these different parameters are unlikely to confer a survival advantage for either HIPEC method.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal method of HIPEC delivery has long been debated. Previous investigations have been limited to small single center retrospective reviews[ 9 , 10 ] or preclinical animal models[ 11 - 13 ]. Therefore, we sought to evaluate the impact of open vs closed HIPEC technique on short- and long-term outcomes, using a large multi-institutional database.…”
Section: Introductionmentioning
confidence: 99%
“…All advantages and disadvantages regarding the choice of technique are listed in Table 4. Despite the different advantages and disadvantages of the delivery techniques, the clinical outcome in terms of survival and morbidity rates is similar [55,56,57]. Differences in intraoperative parameters, such as blood pressure, pulse rate, core temperature, etc., are also not statistically significant between the techniques [55].…”
Section: Parameters Of Hipecmentioning
confidence: 99%